ANALISIS PRODUKSI DAN PENDAPATAN USAHATANI JAGUNG DI KECAMATAN PALOLO KABUPATEN SIGI - Jonh Tomy (Universitas Tadulako, 2013)
This study aims to determine the effect of land, labor, seed, and fertilizer to the physical production of corn and to find out how much income derived from farming corn growers. This research was conducted in the Palolo Subdistrict Sigi Regency. The location determined by purposive research, because it is one area that many cultivated crops of corn. Respondents sample were corn farmers. Respondent performed by Simple Random Sampling Method as many as 30 people from 120 families maize farmers. Data were analyzed using analysis of Cobb - Douglas and revenue analysis. The analysis showed that simultaneously (together) factor land area, the number of workers, seed and fertilizer very significant effect on corn production. Partially, the land area, labor, and fertilizer no real effect on the production of corn. The income received by the farming corn growers during one growing season is Rp. 2,216,596 per 0.78 ha. Key Words : Corn farming. income, production.